Approaches to the Medieval Self Representations and Conceptualizations of the Self in the Textual and Material Culture of Western Scandinavia, c. 800-1500 - Eriksen, Stefka G.; Langsholt Holmqvist, Karen; Bandlien, Bjørn (De Gruyter, 2020)
The self and how it relates to its surrounding world and history is a main concern of the humanities and social sciences. This book addresses the issue by discussing various modes of studying and defining the self, based on a wide span of sources from medieval Western Scandinavia, c. 800-1500, such as archeological evidence, art and architecture, documents, literature, and runic inscriptions.